Transient analysis of multiple straight wires in the presence of a half-space using different time-domain measures. Issue 11 (24th July 2022) - Poljak, D.; Antonijevic, S.; Miller, E. K.
Abstract : The paper deals with a direct time-domain (TD) analysis of multiple wire configurations using various TD measures based on the energy stored in the near field. The currents along the wires are obtained solving the coupled Hallen integral equations. Once the current distribution is determined it is possible to calculate the charge via continuity equation. Knowing the distribution of current and charge along the wires, TD energy measures involving spatial integrals of squared values of transient current and charge, the energy stored in the electric and magnetic fields of wires are evaluated. Then total TD power measure defined as the time derivative of the total energy measure is computed. Finally, according to the definition stemming from the circuit theory the distribution of root-mean-square (RMS) values of transient current is calculated. Some computational examples for transient current, TD energy, and power measures, respectively, and RMS distribution along the wires are presented.